'If you're gonna die, you're gonna die': Young adults' perceptions of sudden unexpected death in epilepsy. (September 2015) - Harden, Jeni; Tonberg, Anissa; Chin, Richard F; McLellan, Ailsa; Duncan, Susan
Objectives: To explore the views and experiences of young adults with epilepsy on the risks associated with, and information giving in relation to sudden unexpected death in epilepsy (SUDEP). Methods: In-depth interviews with 27 young adults (aged 18–29 years) with epilepsy. Results: Participants reported everyday experiences of seeking to control the risk of seizure occurrence or injury from seizures. In contrast, SUDEP was reported in more fatalistic terms as a risk that was considered to be largely unpreventable. Participants stated that information on SUDEP should be given to those with epilepsy, in a consultation, at or soon after the diagnosis, though clinical judgement on patients' readiness was considered important in timing decisions. Many had a limited, sometimes incorrect understanding of SUDEP, yet were satisfied with the information they had received. Very few engaged in independent information seeking on SUDEP, and many deliberately avoided searching for further information. Discussion: Our findings suggest that SUDEP was bracketed off from other aspects of participants' epilepsy, in terms of the meanings attributed to it, perceptions of risk status and ways of coping. SUDEP is a case through which to consider how people give meaning to information about risk of sudden death related to chronic conditions.